ART OF TYEB MEHTA: तैयब मेहता की कला' - Kaur, Kulwinder; Pandey, Anjali (International Journal of Research -GRANTHAALAYAH, 2021)
English : Most of the paintings of internationally renowned painter and sculptor Tyeb Mehta, honored with Kalidas and Padma Bhushan, have been influenced by many incidents in the childhood, Edward Munsch and Kokoshka had a great influence on Tyeb, born in Kheda, Gujarat, in his art style from time to time. But change is seen. In the initial paintings, the expression has been given space, in the medium level pictures, the expression of the space has been replaced by the bifurcated two- dimensional picture and the empty space, the diagonal took its place in the final pictures, under which started drawing pictures in triangles. With festivals, Kali, etc., he was counted among the most expensive artists of India. During his lifetime, he produced very few artifacts and died in 2009. Apart from the sculptor, he was also a film maker. Hindi : कालिदास और पद्म भूषण से सम्मानित अंतरराष्ट्रीय स्तर के प्रसिद्ध चित्रकार और मूर्तिकार तैयब मेहता के चित्रों में से अधिकांश बचपन में कई घटनाओं से प्रभावित रहे हैं, एडवर्ड मुंस और कोकश्का ने अपनी कला में गुजरात के खेड़ा में पैदा हुए तैयब पर काफी प्रभाव डाला था। समय-समय पर शैली। लेकिन बदलाव देखा जाता है। प्रारंभिक चित्रों में, अभिव्यक्ति को स्थान दिया गया है, मध्यम स्तर के चित्रों में, अंतरिक्ष की अभिव्यक्ति को द्विभाजित दो-आयामी चित्र और खाली स्थान से बदल दिया गया है, विकर्ण ने अंतिम चित्रों में अपना स्थान लिया, जिसके तहत त्रिकोणों में चित्र बनाना शुरू किया। त्योहारों, काली आदि के साथ, उन्हें भारत के सबसे महंगे कलाकारों में गिना जाता था। अपने जीवनकाल के दौरान, उन्होंने बहुत कम कलाकृतियों का निर्माण किया और 2009 में उनकी मृत्यु हो गई। मूर्तिकार के अलावा, वह एक फिल्म निर्माता भी थे।